IMPACT OF GROSS DOMESTIC PRODUCT, DOMESTIC PRICE AND EXCHANGE RATES ON INDONESIA’S MANGOSTEEN EXPORTS TO UNITED ARAB EMIRATES - Rianta Chen Yohana Manik; Holpu Ronal Ambarita (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Indonesia exports more mangosteen than any other fruit. Five countries are its export destinations, including the United Arab Emirates. According to data from UN Comtrade, the export volume of Indonesian mangosteen fluctuated from 2019 to 2023. According to experts and previous studies, this fluctuation is due to several factors. Therefore, this quantitative study will analyze the influence of the United Arab Emirates' gross domestic product (GDP), the domestic price of Indonesian mangosteen, and the dollar-to-rupiah exchange rate on Indonesia's mangosteen exports to the United Arab Emirates from 2003 to 2023. Additionally, we aims to analyze whether gross domestic product, Indonesian domestic mangosteen prices, and the dollar-to-rupiah exchange rate jointly influenced Indonesian mangosteen imports to the United Arab Emirates during the same period. The research location was deliberately chosen in Indonesia, and secondary sources were used to collect time series data from 2003 to 2023. Quantitative data analysis was conducted using SPSS 25 and quantitative methods. The study's findings suggest that the United Arab Emirates' gross domestic product, the domestic price of Indonesian mangoes, and the dollar-to-rupiah exchange rates at the same time affect to quantity of mangosteen exported to the United Arab Emirates. Based on a partial test, the United Arab Emirates' gross domestic product had a significantly positive effect on Indonesian mangosteen exports to the United Arab Emirates, with a regression coefficient of 3.398E-6. This indicates that if the United Arab Emirates' gross domestic product increases one US dollar, Indonesian mangosteen exports to the United Arab Emirates will increase to 3.398E-6 kilograms. The domestic price of Indonesian mangosteen had a significantly negative effect on the volume of exports, with a regression coefficient of -398. This indicates that if the domestic price of mangosteen in the UAE increases by Rp 1,000/kg, exports to the UAE decrease by 398,755 kg.The dollar-to-rupiah exchange rate also negatively affects the Indonesian mangosteen export volume to the United Arab Emirates. With a regression coefficient of -95.267, an increase in the dollar exchange rate of 1 US$/Rp results in decline has been observed in the export volume of Indonesian mangosteen. to the United Arab Emirates of 95.267 kg.